Population size matters: The cause & effect of heterogeneous β1AR expression and its influence on receptor internalization. - Langvad, Sylvester Houstrup (UCPH NanoScience - a student research journal, 2018)
In cellular physiology, the impact of heterogeneous receptor expression is a topic that has recently started to receive much attention from the scientific community. However, much is still not understood about the specifics on the ori- gin of this heterogeneity nor how it affects bulk measurements of heterogeneous population. While the literature often acknowledges this heterogeneity, it falls short of offering an explanation of what practical implications this variability may have. In this paper, we examine two methods for evoking protein expression of G Protein-Coupled Receptors, transient transfection and inducible cell lines, and show that these methods have markedly different expression variabilities. While the inducible cell lines have relatively homogeneous expression profiles, the tran- sient transfected cells showed large variability to an extent that bulk measurements of transfected cells may yield misleading data. We hope that the results presented in this paper may inspire future research in the field to fully consider the effects of heterogeneous expression profiles.